Analysis Of The Influence Of Religiosity, Service Quality, And Corporate Image On Customer Loyalty With Trust As An Intervening Variable - NINGSIH, DIAH WURIAH (Jurnal Ekonomi dan Bisnis, 2024)
The research aims to determine the influence of religiosity, service quality, and corporate image on customer loyalty, mediated by trust, considering both direct and indirect effects. The object of this research is BSI KCP Pemalang Sudirman 1, using the accidental sampling technique and Slovin's formula, with a sample of 98 respondents. The testing in this study employed quantitative methods, including instrument testing, validity testing, reliability testing, classical assumption testing, hypothesis testing, path analysis, and the Sobel test. The validity results for each question item of the variables were valid. The reliability results for each question item of the variables were reliable. Partial research results indicate that the variables of religiosity, service quality, and corporate image have a significant effect on customer loyalty. There is a significant influence of religiosity, service quality, and corporate image on customer loyalty with trust as an intervening variable. Furthermore, trust has a significant effect on customer loyalty.